2021
DOI: 10.1002/adem.202100382
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Silicone Rubber Foams Made with Water as Blowing Agent

Abstract: Liquid silicone rubber (LSR) is primarily used in injection molding. Foamed molded parts made of LSR are almost nonexistent because the process reliability of LSR foam injection molding is currently not given. It makes sense to have suitable foaming processes for this material as well, because the density of this elastomer is about 1.15 g cm−3. With the injection molding process presented herein for foaming LSR, density reductions of up to 40% can be achieved. In this process, up to 3% by weight of water is ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The third conclusion is the very homogeneous cell structure over the entire sample. Compared to other foaming methods, such as water foamed LSR samples in [ 13 ], the size of the pores at different positions is very similar. The homogeneous cell structure results from the nature of the microspheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third conclusion is the very homogeneous cell structure over the entire sample. Compared to other foaming methods, such as water foamed LSR samples in [ 13 ], the size of the pores at different positions is very similar. The homogeneous cell structure results from the nature of the microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…With other blowing agents such as water (cf. [ 13 ]), multiple nucleation centers can grow together, resulting in very inhomogeneous cell structures. In the case of microspheres, on the other hand, the shells touch each other in the process, but the gas remains separated.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of injection molding of LSR, it has been found that with water, an increase in the process temperatures results in a higher weight reduction and an increase in the Shore A hardness. In addition, the number of pores increases, but not the pore size [20].…”
Section: Introductionmentioning
confidence: 94%
“…Here, gases such as carbon dioxide and nitrogen or liquids such as water can be injected into the extrusion process [15]. In the case of water, the blowing agent can also be incorporated into the rubber mixture using a carrier substance such as silica, which means that additional foaming equipment is not required [20]. The alternative to chemical blowing agents is physical blowing agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation